The Ethics of Self-Care in Higher Education - Bryan, Venise; Blackman, Galicia (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2019)
In this literature review, we seek to work through the implicit dilemma of the ethics of self-care in higher education. The pressure to meet the multiple demands of higher education, alongside personal goals and diverse value-systems, can make it difficult to prioritize self-care. Individuals in higher education often seek to meet their goals through self-sacrificing practices which can lead to stress and burnout. We used an interpretive inquiry approach and authentic leadership theory to present our conclusion, that self-care in higher education is an ethic, and integral to meeting higher education goals. Authentic leadership promotes communion with self and the resultant effect of attaining balance. This article presents selected self-care practices which can support emotional, mental, social, and physical needs in higher education.